2001
DOI: 10.1161/hc3901.095771
|View full text |Cite
|
Sign up to set email alerts
|

Single Oral Dose of Geranylgeranylacetone Induces Heat-Shock Protein 72 and Renders Protection Against Ischemia/Reperfusion Injury in Rat Heart

Abstract: Background-Induction of heat-shock proteins (HSPs) results in cardioprotection against ischemic insult. Geranylgeranylacetone (GGA), known as an antiulcer agent, reportedly induces HSP72 in the gastric mucosa and small intestine of rats. The present study tested the hypothesis that oral GGA would induce HSP72 in the heart and thus render cardioprotection against ischemia/reperfusion injury in rats. Methods and Results-Cardiac expression of HSPs was quantitatively evaluated in rats by Western blot analysis. Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
163
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(175 citation statements)
references
References 32 publications
11
163
1
Order By: Relevance
“…Thus it seems unlikely that systemic caspase inhibitors or JNK inhibitors will be developed into safe and viable cotherapies aimed at inhibiting aminoglycoside-induced ototoxicity. However, it is possible to safely induce Hsp70 in the whole organism, either by experimental manipulation (heat stress) (Dechesne et al 1992;Yoshida et al 1999;Sugahara et al 2003) or by administration of a therapeutic agent (Hirakawa et al 1996;Ooie et al 2001;Oda et al 2002;Mikuriya et al 2005;Sone et al 2005). In order to begin to develop Hsp70 as an otoprotective therapy against aminoglycoside-induced hearing loss, a safe method of Hsp70 induction is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it seems unlikely that systemic caspase inhibitors or JNK inhibitors will be developed into safe and viable cotherapies aimed at inhibiting aminoglycoside-induced ototoxicity. However, it is possible to safely induce Hsp70 in the whole organism, either by experimental manipulation (heat stress) (Dechesne et al 1992;Yoshida et al 1999;Sugahara et al 2003) or by administration of a therapeutic agent (Hirakawa et al 1996;Ooie et al 2001;Oda et al 2002;Mikuriya et al 2005;Sone et al 2005). In order to begin to develop Hsp70 as an otoprotective therapy against aminoglycoside-induced hearing loss, a safe method of Hsp70 induction is required.…”
Section: Discussionmentioning
confidence: 99%
“…GGA has been safely used in Japan in the clinical treatment of gastric ulcers (Shirakabe et al 1995;Nagasawa et al 1998;Miyake et al 2004;Qian et al 2007). GGA has been shown to induce Hsp70 in variety of tissues, including the gastric mucosa, heart, liver, brain, and cochlea (Hirakawa et al 1996;Ooie et al 2001;Oda et al 2002;Mikuriya et al 2005;Sone et al 2005). Recent in vitro studies have suggested a protective effect of GGA against aminoglycoside-induced ototoxicity (Takumida and Anniko 2005;Sano et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, transgenic overexpression of HSP70 in the myocardium confers protection against both myocar- dial stunning and infarction following ischemia (14,21,28,30,42), whereas pharmacological induction of HSP70 in the myocardium also imparts resistance to ischemia (15,20,29,46). Furthermore, heat stress induction of HSP70 in the myocardium is associated with the development of "cross tolerance" to subsequent prolonged ischemia (4,43).…”
Section: Discussionmentioning
confidence: 99%
“…GGA is an isoprenoid that is used clinically for the treatment of gastritis and gastric ulcers (Murakami et al 1981(Murakami et al , 1982a. GGA induces Hsp70 in a variety of tissues, including the gastric mucosa, heart, liver, brain, and cochlea (Hirakawa et al 1996;Ooie et al 2001;Oda et al 2002;Mikuriya et al 2005;Sone et al 2005). In designing a therapy aimed at the prevention of druginduced hearing loss and/or balance disorders, Hsp70 induction by GGA or other pharmaceutical inducers may represent a rational alternative to induction by local and whole-body heat stress.…”
Section: Figmentioning
confidence: 99%